Penıngkatan Pendapatan Petanı Berbasıs Pembangunan Berkelanjutan Melaluı Inovası Teknologı dan Akses Pasar - Hasriani, Hasriani; Sukriming Sappareng; Hamjah Abdul Malik (SINTA Journal (Science, Technology, and Agricultural), 2025)
The purpose of this study is to analyze the influence of technological innovation on increasing farmer income in Rante Angin District, North Kolaka Regency (especially technology related to production efficiency and sustainable natural resource management), to identify the role of market access in increasing farmer income (both through local and regional market access and how it contributes to farmer economic sustainability), and to explore the interaction between technological innovation and market access in increasing farmer income and its impact on achieving sustainable development goals. The research method used is quantitative research, using primary and secondary data obtained through observation data collection techniques, interviews, questionnaires and literature studies which are then analyzed using multiple analysis methods. The results of this study found several things, namely: 1) The use of agricultural tools and machinery (alsintan) has been proven to have a positive impact on increasing farmer income; 2) The use of modern fertilizers such as compound fertilizers (NPK), biofertilizers, and liquid organic fertilizers, plays an important role in increasing crop yields by improving soil fertility and plant nutrient absorption efficiency; 3) The use of alsintan has a positive and significant effect on farmer income; 4) Innovative Planting Systems have a positive and significant effect on farmer income; 5) Access to digitalization systems has a significant and directional impact on farmers' income, and; 6) Irrigation and digitalization access play an important role in improving farmers' welfare. Conclusion: The use of innovative agricultural technology and good market access has a positive impact on increasing farmers' income in Ranteangin District, North Kolaka Regency